2018
DOI: 10.1503/cmaj.171390
|View full text |Cite
|
Sign up to set email alerts
|

“All my relations”: experiences and perceptions of Indigenous patients connecting with Indigenous Elders in an inner city primary care partnership for mental health and well-being

Abstract: BACKGROUND: Mental health services in urban settings generally have not been adapted to serve the needs of Indigenous patients. We explored how patients' encounters with Indigenous Elders affected their overall mental health and well-being to identify therapeutic mechanisms underlying improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 31 publications
4
48
0
Order By: Relevance
“…In our study, healthcare staff also recognized the critical importance of cultural connectedness for the health and wellbeing of many of their Indigenous patients, and welcomed the opportunity for Elders to be the facilitators of culture within the clinic. Our findings add to those of others suggesting positive associations between cultural connectedness and Indigenous health, wellbeing, healing, self-determination, belonging, knowledge, empowerment and self-esteem, and identity [21,23,[34][35][36][37]. Cultural interventions in relation to mental health and addictions have been studied far more in comparison to other health conditions, particularly pregnancy-related health.…”
Section: Several Of Thesupporting
confidence: 75%
“…In our study, healthcare staff also recognized the critical importance of cultural connectedness for the health and wellbeing of many of their Indigenous patients, and welcomed the opportunity for Elders to be the facilitators of culture within the clinic. Our findings add to those of others suggesting positive associations between cultural connectedness and Indigenous health, wellbeing, healing, self-determination, belonging, knowledge, empowerment and self-esteem, and identity [21,23,[34][35][36][37]. Cultural interventions in relation to mental health and addictions have been studied far more in comparison to other health conditions, particularly pregnancy-related health.…”
Section: Several Of Thesupporting
confidence: 75%
“…Many of the cultural counsellors and Elders involved in these programs are in high demand in their respective communities, but not recognized as professionals by mainstream counselling organizations or licensing authorities. This study supports a call for the equitable inclusion of cultural counsellors in the strategy to improve care of Indigenous clients in the Canadian health care system (Hadjipavlou et al, 2018). Land-based interventions have the potential to draw on local strengths and keep people who need help close to home, instead of being sent to larger communities for mental health services (GNWT, 2014).…”
Section: Land-based Healing and Wellnesssupporting
confidence: 65%
“…The narratives presented highlight the concern that mental health service provision still operates in a westerndominated discourse, compartmentalizing services and creating a narrow view of mental health, and more specifically what practices are considered counselling and therapy (Hadjipavlou et al, 2018). This discourse is largely defined by western understandings of mental health and the language of evidence-based practice (EBP), which is still so often interpreted as empirically supported treatments (Carter & Goodheart, 2012;Laska et al, 2014).…”
Section: Barriers To Accessing Land-based Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies have shown the potential of peer groups to reduce feelings of loneliness and hopelessness (Brown & Day, 2008), and prison visitation has been shown to improve mental health and reduce recidivism (Albertie et al, 2017;De Claire & Dixon, 2015;Duwe & Johnson, 2016). For Indigenous Peoples, ongoing relationships with Elders has immense benefits (Hadjipavlou et al, 2018;Tu et al, 2019;Waldram, 1997), including those who are incarcerated (Willis & Moore, 2008). Indigenous youth with previous engagement with the colonial justice system have been found to benefit from youth-specific programming in which they engaged with Indigenous Knowledge Keepers, value systems, and culture, which were found to enhance feelings of pride in cultures and identities (Hansen, 2015).…”
Section: Introductionmentioning
confidence: 99%